PROMOTIONAL OPPORTUNITIES FOR ENHANCING SALES IN COSMETICS PRODUCTION SECTOR THROUGH SOCIAL MEDIA PLATFORMS - Jakštiene, Sandra; Meište, Ruta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The paper deals with the promotional opportunities enhancing sales in the cosmetics production sector through social media platforms (SMPs). This topic holds significant relevance in the contemporary business landscape. Firstly, in the digital age, consumer behavior is evolving rapidly, with SMPs becoming integral in shaping purchasing decisions. Understanding the dynamics of consumer engagement and preferences on these platforms is crucial for cosmetics producers seeking to optimize their promotional strategies. Moreover, as the cosmetics industry increasingly transcends geographical boundaries, social media provides a global platform for reaching diverse audiences. Understanding how to tailor promotional efforts to different demographics and cultures is vital for international market expansion, and this study addresses these considerations. The aim of the research is to analyse the promotional opportunities for enhancing sales in the cosmetics production sector through social media platforms. Methods: analysis of scientific literature, questionnaire survey, analysis of information sources, data summarisation, graphical representation. The results obtained through the questionnaire survey indicate a relatively low level of popularity in the analyzed cosmetics production sector. Consequently, respondents encountered challenges in providing comprehensive responses due to this limited awareness. The survey further highlights that the company primarily employs a modest set of fundamental sales promotion methods on social networks.